Iraq's Earth Map: An Innovative Tool for Quickly Conducting Enhanced Land Monitoring and Climate Assessment (Iraqi National Journal of Earth Science (INJES), 2026)
The current paper cites the Food and Agriculture Organization's (FAO) Earth Map application as a major development in data analysis and environmental monitoring in Iraq. The article outlines the urgent environmental issues that the nation faces, such as water scarcity, land degradation, and desertification, which all need efficient monitoring and assessment techniques. Without the need for coding expertise, Earth Map is a web-based geospatial application that gives users quick access to a variety of geospatial data and analytic tools. The software successfully visualizes and analyzes geographic layers by grouping data into over 15 subject areas such as biodiversity, land use, climate, and greenhouse gas emissions. The application makes use of the Google Earth Engine (GEE) API to provide high-resolution visualizations and real-time information, allowing users to do in-depth analysis and dynamically monitor environmental changes. The study highlights the tool's capacity to retrieve time series data and generate zonal statistics, both of which are essential for comprehending the dynamics of environmental parameters over time. Furthermore, Earth Map has tools like the Imagery Compare tool that let users monitor locations using different Earth observation sources in near real time. Although the Earth Map tool has many advantages, the article also points out some of its drawbacks, such as the requirement for certain technical know-how, possible gaps in the data quality, and difficulties in combining information from remote sensing and ground-based data. To optimize the tool's efficacy, the authors advise strengthening data integration, assuring frequent updates, and augmenting user training. To sum up, the Earth Map tool is a revolutionary method for environmental monitoring in Iraq that offers the public, scholars, and policymakers invaluable information. Earth Map seeks to assist evidence-based decision-making, promote sustainable development, and increase climate resilience in the area by making vital data and analysis tools more accessible.
Keywords: Earth Map, Remote Sensing, Climate Assessment, Geospatial Analysis, Environmental Data.